2019
DOI: 10.1049/el.2019.1031
|View full text |Cite
|
Sign up to set email alerts
|

Implantable CMOS image sensor with incident‐angle‐selective pixels

Abstract: Angle-selective pixels fabricated by using metal layers of the image sensor chip are proposed. Four incident-angle-selective pixels share one aperture. The selective pixel has a peak at 40°and full width at half maximum of ∼23°. An image sensor composed of normal and angle-sensitive pixels was designed and fabricated. The reconstruction of a high-resolution image from the blurred image using five different views is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In this device, a simple lensless imaging is adopted, and spatial resolution is impaired by thickness of the filter layer. As regards fluorescent observations that require high spatial resolution, some measures must be taken such as the use of configuration capable of detecting incidence angle distribution combined with image reconstruction 17,18 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this device, a simple lensless imaging is adopted, and spatial resolution is impaired by thickness of the filter layer. As regards fluorescent observations that require high spatial resolution, some measures must be taken such as the use of configuration capable of detecting incidence angle distribution combined with image reconstruction 17,18 …”
Section: Resultsmentioning
confidence: 99%
“…As regards fluorescent observations that require high spatial resolution, some measures must be taken such as the use of configuration capable of detecting incidence angle distribution combined with image reconstruction. 17,18 On the other hand, detected signals are very weak everywhere except for the beads, even with normal incidence of excitation light. This is indicative of high performance of excitation light rejection; thus, a high-performance hybrid filter can be installed on the image sensor by a transfer method to deal with weak fluorescence in living organisms.…”
Section: Examples Of Fluorescent Observationmentioning
confidence: 99%
“…Meanwhile, because fluorescent light is spatially and temporally incoherent, holographic-based post-image processing cannot be used to achieve a superpixel resolution as in the Brightfield lensless device [ 38 ]. One possible way to overcome this is to obtain light-field information using angle-selective pixels [ 39 , 40 ]. Furthermore, despite the limited illumination requiring multiple, rather than single, irradiation spots to acquire the entire imaging area, the in vitro experiment confirmed that the fabricated device could identify the bright pattern of GFP emission from the brain slices.…”
Section: Discussionmentioning
confidence: 99%
“…In this technique, pixels, which normal and angle-selective, detect different incident angles via the designed metal aperture structure. As a result, the image reconstruction process can acquire a spatial resolution close to the pixel pitch [31].…”
Section: Fluorescent Image From Microspheresmentioning
confidence: 99%